The relationship between food insecurity, purchasing patterns and perceptions of the food environment in urban slums in Ibadan, Nigeria - Temitope Ilori; Nicola Christofides; Laurel Baldwin-Ragaven (BMC Nutrition, 2024)
Abstract Background Rapid urbanisation without concomitant infrastructure development has led to the creation of urban slums throughout sub-Saharan Africa. People living in urban slums are particularly vulnerable to food insecurity due to the lack of physical and economic accessibility to food. Hence, it is important to explore how vulnerable groups living in slums interact with the food environment. This study assessed the relationships between food insecurity, including restrictive coping strategies, food purchasing patterns and perceptions about the food environment among dwellers of selected urban slums in Ibadan, Nigeria. Methods This community-based cross-sectional study was conducted with people responsible for food procurement from 590 randomly selected households in two urban slums in Ibadan. Food insecurity and restrictive coping strategies were assessed using the Household Food Insecurity Access Scale and the Coping Strategy Index, respectively. We examined purchasing patterns of participants by assessing the procurement of household foodstuffs in different categories, as well as by vendor type. Participants’ perceptions of the food environment were derived through a five-item composite score measuring food availability, affordability and quality. Chi-square tests and logistic regression models analysed associations between food insecurity, purchasing patterns and perceptions of the food environment. Results The prevalence of food insecurity in the sample was 88%, with 40.2% of the households experiencing severe food insecurity. Nearly a third (32.5%) of the households used restrictive coping strategies such as limiting the size of food portions at mealtimes, while 28.8% reduced the frequency of their daily meals. Participants purchased food multiple times a week, primarily from formal and informal food markets rather than from wholesalers and supermarkets. Only a few households grew food or had livestock (3.2%). Food insecure households had a lower perceived access to the food environment, with an approximate 10% increase in access score per one-unit decrease in food insecurity (AOR = 0.90, 95% CI: 0.84, 0.96). The most procured foods among all households were fish (72.5%), bread (60.3%), rice (56.3%), yam and cassava flours (50.2%). Food-secure households procured fruit, dairy and vegetable proteins more frequently. Conclusion Food insecurity remains a serious public health challenge in the urban slums of Ibadan. Perceptions of greater access to the food environment was associated with increasing food security. Interventions should focus on creating more robust social and financial protections, with efforts to improve livelihoods to ensure food security among urban slum-dwellers.